A review of mushrooms in human nutrition and health. (November 2021) - Rizzo, Gianluca; Goggi, Silvia; Giampieri, Francesca; Baroni, Luciana
Abstract: Background: mushrooms are traditionally used as a food ingredient and in folk medicine. Many in vitro and animal studies have reported their potential health effects, but without any clear application in human health. Although they have a worldwide history of use in dishes and folk medicine, mushroom extracts are commonly taken as supplements but need to be evaluated regarding clinical effects and safety, in particular among patients searching for further efficacy for their disease beside pharmacological treatments already prescribed. Scope and approach: this review summarizes available data from the scientific literature about the nutritional and effects of mushrooms on human health by selecting clinical studies on humans in English. At the same time, the safety profile and unwanted effects were highlighted. Key findings and conclusions: in spite of their wide use among populations, data on humans were scant and did not justify extensive use without more well-designed trials on mushroom efficacy. Overall, their use seems to be safe, but with some side effects, easily reversible after intake interruption. Nutritional use seems promising for coping with the energy surplus of the Western countries and could be useful for some nutritional aspects. Highlights: Mushrooms are widely used in nutrition and for medical purposes. Medical mushroom use is very popular among cancer patients. Despite their history of use, safety profile and clinical use are rather unknown. There may be an overuse of mushroom extracts as supplements among patients.